Role Of a Unified IT Network as The Foundation for The Digital Transformation of Multi-Profile Facilities - Chata Marat Muratuly (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
At present, digital transformation acts as a determining element in maintaining competitiveness and increasing the operational efficiency of facilities of various purposes—from production complexes to socio-administrative structures. The study is aimed at a comprehensive examination of the role of a unified IT network as a basic systemic framework that ensures the implementation of this transformation. The purpose of the work is to identify the fundamental design principles and to demonstrate the strategic significance of a convergent network infrastructure for the coherent integration of heterogeneous engineering, operational, and business systems. The methodological basis of the research relies on a systems analysis of contemporary scientific literature over the period, the examination of relevant regulatory and standard requirements, and the practical deconstruction of a case involving the deployment of a comprehensive IT infrastructure at a strategically important facility—the National Company Kazakhstan Garysh Sapary. As a result of the analysis, a conceptual model of a unified network has been formed, as well as a rationale for its key advantages, including the improvement of operational efficiency, the rationalization of resource use, and the strengthening of cybersecurity levels. The scientific novelty consists in interpreting the unified IT network not only as a technical element but as a strategic asset that creates synergistic effects when digital technologies are introduced. The obtained conclusions and formulated practical recommendations are of value to organization leaders, IT directors, system architects, and engineering specialists who design and modernize the infrastructures of multi-profile facilities within the context of the developing digital economy.